THE INFLUENCE OF NIM AND NPL ON ROA AT NATIONAL PRIVATE BANKS IN INDONESIA FOR THE PERIOD 2021-2023 - Diki Abramsa Putra Ginting; Krisna Marpaung, Fenny (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The level of profitability or the capability of an institution to generate profit is a quantitative indicator used in evaluating financial performance, especially in assessing the company's ability to obtain a profit that is considered appropriate. The main focus of the preparation of financial statements lies in the achievement of this profit. This study is intended to analyze the extent to which Net Interest Margin (NIM) and Non Performing Loan (NPL) have an effect on Return on Assets (ROA) at National Private Commercial Banks in Indonesia. This study adopts a quantitative approach, with data collection techniques carried out through the documentation method. Data analysis was carried out using multiple linear regression, determination test (R²), and hypothesis testing. As the results of the regression model estimation, the equation obtained is: Y = -0.103 + 0.494X₁ - 0.234X₂. The value (R²) was recorded at 0.472, which indicates that the NIM and NPL variables explain around 47.2% of the variation in ROA, while the remaining 52.8% is influenced by other factors not included in the model. The results of the partial test (t-test) show that both NIM and NPL have a high influence individually on ROA. Meanwhile, the results of the F test show a sig. 0.000 which is <0.05, so it is concluded that collectively NIM and NPL have an influence on ROA at National Private Commercial Banks.